A Communication of Persuasion in the Management of Character Emotions through Hikayat Nakhoda Muda (Malay Literature, 2022)
Emotions play an essential role in human life because emotions affect a large part of life. Emotions are God’s gift to humans that will give a variety of reactions, response, and behaviours. Emotions will guide and colour the path of human life. The construction of positive and negative emotions depend on the acceptance and interpretation of the individual towards an event experienced. Positive emotions will lead to positive life and thoughts. On the other hand, negative emotions will lead to an unmanageable life with no emotional control and rowdy behaviour. If a human being is emotionally negative, the individual will have emotional disorder. Emotional disorder needs to be controlled and dealt with promptly without being protracted and prolonged. Communication is one of the steps in dealing with emotional problems. In this case, this study will analyse the persuasive communication strategy in managing character emotions through the Hikayat Nakhoda Muda used as study data. The research also use the Social Judgement Theory to strengthen the arguments of discussion. The results found that the persuasive communication strategy is divided into two: persuasive verbal communication and persuasive non-verbal communication. Therefore, this study proves that the implementation of persuasive communication successfully controls and manages disturbed and unstable emotions.